Numerical Modelling of Mechanical Phenomena in the Gantry Crane Beam. (2017) - Sowa, Leszek; Saternus, Zbigniew; Kubiak, Marcin
Abstract: The mathematical model and numerical simulations of the mechanical phenomena in the gantry crane are presented in this paper. The design of modern mechanical constructions is a complex task that requires use of appropriate tools. Such a modern tool, that gives a broad opportunity to analyze strength parameters of designed structures, is numerical simulation which uses the various numerical methods. Here the problem was solved by the finite element method. The analysis of the stresses and strains of the structure of gantry crane was made using the advanced software with highly efficient possibilities of modeling. Motion of the crane trolley along the beam was also taken into account in the study. The research performed, allows the evaluation of the stress state, pointing out the critical areas and values which are made in order to increase the strength of the structure of the gantry crane. The results of numerical simulation are presented in the form of the fields of Huber-Misses stress for the selected location of the crane trolley.